Microbial endophytes and compost improve plant growth in two contrasting types of hard rock mining waste. Issue 6 (12th May 2023) - Creamer, Courtney A.; Leewis, Mary-Cathrine; Governali, Francesca C.; Freeman, John L.; Gray, Floyd; Wright, Emily G.; Foster, Andrea L.
Abstract: The re-vegetation of mining wastes with native plants is a comparatively low-cost solution for mine reclamation. However, re-vegetation fails when extreme pH values, low organic matter, or high concentrations of phytotoxic elements inhibit plant establishment and growth. Our aim was to determine whether the combined addition of municipal waste compost and diazotrophic endophytes (i.e., microorganisms that fix atmospheric N2 and live within plants) could improve plant growth, organic matter accumulation, and phytostabilization of trace element contaminants in two types of hard rock mine waste. We grew a widespread native perennial grass, Bouteloua curtipendula, for one month in alkaline waste rock (porphyry copper mine) and tailings (Ag-Pb-Au mine, amended with dolomite) sourced from southeastern Arizona, United States. B. curtipendula tolerated elevated concentrations of multiple phytotoxic trace elements in the tailings (Mn, Pb, Zn), stabilizing them in roots without foliar translocation. Adding compost and endophyte seed coats improved plant growth, microbial biomass, and organic matter accumulation despite stark differences in the geochemical and physical characteristics of the mining wastes. The widespread grass B. curtipendula is a potential candidate for re-vegetating mine wastes when seeded with soil additives to increase pH and with microbial and organic amendments to increase plant growth. NOVELTY STATEMENT: This study quantifies improvements to plant growth, soil fertility, and trace element stabilization with a municipal waste compost topdressing and diazotrophic endophyte seed coating in two common hard rock mining wastes of the western United States. It establishes that a widespread perennial grass, Bouteloua curtipendula, can grow despite high concentrations of phytotoxic trace elements and minimal soil nutrients, and stabilizes trace elements on or in its roots, making it a suitable option for re-vegetation or phytostabilization of hard rock mining wastes.